Komunikasi Pemasaran terhadap Minat Beli Konsumen - Fikriansyah, Fikriansyah; Christantyawati, Nevrettia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to prove that marketing communications conducted by PT. Pinang Mas Bersaudara can attract consumer purchasing interest. This study uses a quantitative approach with data collected through questionnaires from 25 consumers who have transacted with PT. Pinang Mas Bersaudara. The results of the study found that marketing communications have a significant influence on consumer purchasing interest. This finding provides a deep understanding of the importance of marketing communications strategies in shaping consumer purchasing interest. It includes guidance for PT—Pinang Mas Bersaudara in designing more effective marketing strategies. Keywords: Marketing Communications, Purchase Interest, AIDA Marketing